Analysis of Volleyball's Deadly Smash in the PROLIGA Match at GOR Jayabaya Kediri - Sonia Nirhaini; Moh. Nurkholis; Rizki Burstiando (CV. Nusantara Sporta, 2024)
This research examines the most effective volleyball smash techniques to maximize points in the PROLIGA semi-final at GOR Jayabaya Kediri. Using a quantitative and descriptive approach, data was collected through observation, documentation, and a questionnaire from all 56 players across the 4 semi-final teams. The analysis revealed variations in attack quality, with the open spike being the most effective, followed by the back attack, quick attack, serve, and semi. The findings provide valuable insights into the effectiveness of different attack strategies in the PROLIGA semi-final matches.